Global burden of chronic kidney disease due to diabetes mellitus, 1990-2021, and projections to 2050 - Ma, Xiao; Liu, Rong; Xi, Xiang; Zhuo, Hui; Gu, Yiwei (Frontiers in Endocrinology, 2025)
IntroductionChronic kidney disease (CKD) is a serious complication of diabetes, and the global burden of the disease is gradually increasing.MethodsThis study systematically analyzed the trends and future projections of the worldwide burden of chronic kidney disease caused by type 1 and type 2 diabetes mellitus based on the Global Burden of Disease Study (GBD) using data from 1990 to 2021. Number of deaths, Age-standardized mortality rates, disability-adjusted life years (DALYs), and age-standardized DALYs rate were used to estimate the disease burden. The study used Estimated Annual Percentage Changes (EAPCs) to calculate trends in the burden of each disease subtype and different regions and assessed the impact of various age groups and metabolic factors on chronic kidney disease due to diabetes. The ARIMA model was further used to predict the burden of Diabetic nephropathy from 2022 to 2050.ResultsThe results of the study showed that the burden of Diabetic nephropathy and its EAPCs varied significantly in distribution across different Sociodemographic Index subgroups of countries as well as among 204 countries and regions worldwide. In addition, the influence of different age groups and metabolic factors on the burden of Diabetic nephropathy also showed significant variability. The effects of metabolic factors on the number of deaths and mortality were positively correlated with age. Different metabolic factors have different effects on the mortality of CKD due to type 1 diabetes and CKD due to type 2 diabetes. The ARIMA model predicts that the global burden of Diabetic nephropathy will continue to increase in the absence of interventions.ConclusionsTo effectively manage CKD caused by diabetes, more accurate and cost-effective diagnostic tools and interventions are needed in the future, especially in low - and middle-income countries with poor healthcare resources.